Making Light - Knapp, Raymond (2018)
In Making Light Raymond Knapp traces the musical legacy of German Idealism as it led to the declining prestige of composers such as Haydn while influencing the development of American popular music in the nineteenth century. Knapp identifies in Haydn and in early popular American musical cultures such as minstrelsy and operetta a strain of high camp-a mode of engagement that relishes both the superficial and serious aspects of an aesthetic experience-that runs antithetical to German Idealism's musical paradigms. By considering the disservice done to Haydn by German Idealism alongside the emergence of musical camp in American popular music, Knapp outlines a common ground: a humanistically based aesthetic of shared pleasure that points to ways in which camp receptive modes might rejuvenate the original appeal of Haydn's music that has mostly eluded audiences. In so doing, Knapp remaps the historiographical modes and systems of critical evaluation that dominate musicology while troubling the divide between serious and popular music.